Efficiency and regulation of gasoline electric generator - Carlson, Torje S.; Stoddard, Albert D.; Dow, Jay L. (My University, 1906)
Introduction: The dynamo tested is a 1.5 K.W. machine generating 115 volts at a speed of 1850 R.P.M. and is short shunt compound wound. It is constructed so as to require little care, having self oiling ring bearings and brushes that do not require shifting with increase of load. The terminal block on the side of the machine is arranged so simply that no mistake could be made in making the connections. External Characteristic. The curve following shows the external characteristic of the dynamo. In obtaining the data for this curve the dynamo was run at constant speed. The rheostat in the shunt field was adjusted so that a voltmeter placed across the terminals reads 110 volts when the dynamo is running without load. The position of the rheostat arm is not changed during the test. A variable resistance and an ammeter are placed in the external circuit. The resistance is decreased, thus increasing the load until the limit of the machine is reached. Readings are taken simultaneously of line amperes and terminal volts for a number of intermediate points. This data is plotted with terminal volts as ordinates and line amperes as abscissas. The object of compounding a dynamo is to maintain a constant voltage at some point on the circuit. The voltage of a shunt dynamo gradually falls as the load increases, therefore in order to maintain a constant potential regulation of the rheostat would be necessary. By compounding the regulation is automatic and no adjustment of the rheostat is necessary.
Citation: Carlson, Torje S., Stoddard, Albert D., and Dow, Jay L. Efficiency and regulation of gasoline electric generator. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Gasoline Electric Generator; Dynamo; Theses